Participatory Geographic Information Systems and Participatory Rural Appraisal Tools for Irrigation Water Management at the Periyar Main Canal Command Area – A Case Study on the Kottampatti Village, Madurai District - Hari Pragash, K. P. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This study is an attempt to provide a solution for a Real-world Problem. Making the farmers to participate in the problem-solving process, which is a participatory approach and PRA Tools are used for it. PGIS tool is easy to use and to interpret the results and to get the output for the given input by the farmers themselves. Geographical Information System (GIS) has been established as a powerful tool for planning and decision-making process. The participation of local farmers at different stages of data input in GIS enables the researcher or a planner to produce a holistic and efficient output in the process of participatory planning and to build an archive of local knowledge that leads to understand the local community fabric and facilitates the project objectives. Participatory GIS is a spontaneous fusion of participatory forms of developmental planning with modem information technologies. Concerted effort was made for mapping natural resources through participatory approach and Participatory GIS (PGIS) aims to use the spatial knowledge of people at local level. The spatial representation of local knowledge facilitates participatory decision- making processes. The use of local knowledge and perception of farmers can help in creating an outline for developmental plans. It can contribute to the empowerment of farmers in solving developmental problems. The Periyar Main Canal Command Area (PMCCA), under the administration of Dindigul, Madurai and Sivagangai districts, is selected for the present study to understand the problem of the farmers. The aim of the study is to understand the irrigation facilities and to analyze the problems in Irrigation Water Management (IWM) using PGIS in Kottampatti village. Participatory maps are prepared by the farmers and are used as input in GIS. Further various methods of Participatory Rural Appraisal (PRA) like Transect Walk, Focus Group Discussion, Participatory Mapping and Ranking Methods shall be used in the study. The problems existing in the study area includes shortage of water for irrigation, inadequate price for agricultural produce, inadequate labor and ineffective water user’s association. Finally, the study aims to conclude with suggestive measures that could be taken for the improvement of irrigation facilities for better cultivation in the study area. This methodology can be applied for any study area for better irrigation water management. PGIS and PRA analysis has good performance towards irrigation Management.